Tingkat Pengetahuan Remaja Putri Tentang Dampak Pernikahan Dini Terhadap Kesehatan Reproduksi - Winda Ratna Dewi; Idawati, Idawati; Nur Hidayat; Risna Susanti; Nur Azmi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Early marriage (marriage to teenagers under the age of 20) is still widely encountered in today's era. One of the reasons is a lack of knowledge about the impact of early marriage on reproductive health. The uterus has not fully developed, triggering an abortion or miscarriage. The risk experienced by mothers in the form of reproductive problems in women and the risk of dying during childbirth is around 35 (55%), miscarriage 32 (17.1%), the risk that occurs in babies with low birth weight is 73%. This research uses several sources including searching several journals through (Google Shcoolar) with the Literature review method. Early marriage is carried out by someone who is on average under 19 years old who on average is not ready in various aspects of marriage. This is likely to have an impact on reproductive health for both women and men. Therefore, it requires preparation from various aspects in carrying out the wedding so that efforts to.